Recent Advances in Information Technology RAIT-2014 Proceedings - Biswas, G. P; Mukhopadhyay, Sushanta (Advances in Intelligent Systems and Computing, 2014)
The book is based on the research papers presented in Second International Conference on Recent Advances in Information Technology (RAIT 2014), held at Indian School of Mines, Dhanbad, India. It provides the latest developments in the area of information technology and covers a variety of topics, including Advanced Algorithm Design and Analysis, Algorithmic Graph Theory, Artificial Intelligence, Bioinformatics, Circuit Design Automation, Computational Biology, Computational Mathematics, Cryptology, Data Compression, Database Management System, Data Mining, E-Applications, Embedded System, Information and Network Security, Information Retrieval, Internet Computing, etc. The objective is to familiarize the reader with the latest scientific developments that are taking place in various fields and the latest sophisticated problem solving tools that are being developed to deal with the complex and intricate problems that are otherwise difficult to solve by the usual and traditional methods.